Silicene growth on Ag(110) and Ag(111) substrates reconsidered in light of Si–Ag reactivity. (25th January 2021) - Colonna, S; Flammini, R; Ronci, F
Abstract: Silicene, the 2D silicon allotrope analogue of graphene, was theoretically predicted in 1994 as a metastable buckled honeycomb silicon monolayer. Similarly to its carbon counterpart it was predicted to present an electronic structure hosting Dirac cones. In the last decade a great deal of work has been done to synthesize silicene and exploit its properties. In this paper we will review our research group activity in the field, dealing in particular with silicon-substrate interaction upon silicon deposition, and discuss the still debated silicene formation starting from the chemistry of silicon unsaturated compounds.